Role of agricultural land practices in the behaviour of nitrates in groundwater - Jayarathne, A.; Bonotto, D. M. [UNESP]; Wijesiri, B.; Goonetilleke, A. (Springer Nature, 2022)
Nitrate contamination is a major issue in aquifers that are being exploited for drinking water. Exceeding maximum contamination levels (MCL) of nitrates in drinking water can cause acute and chronic health problems. In agricultural areas, aquifers are vulnerable to nitrate contamination due to the excessive use of fertiliser. This research study investigated the potential impacts of anthropogenic nitrates on the giant Guarani Aquifer System (GAS) in Brazil, where nitrogen-based fertiliser use had doubled from 2005 to 2016. The study results indicated that there exists two different systems for the behaviour of nitrates in groundwater, above and below a 150 m depth of the aquifer. For the aquifer depth above 150 m, Cl− (positive influence) and F− (negative influence) were found to significantly influence NO3− contamination (p < 0.05). However, statistically significant relationships between NO3− and other influential factors were not found for the aquifer depth below 150 m. Even though agricultural practices do not pose a direct impact on NO3− contamination of groundwater, it was evident that anthropogenic inputs of NO3− could elevate the concentrations in the aquifer depth reaching 150 m.
Keywords: Agricultural land use; Drinking water; Groundwater pollution; Nitrate contamination; Nitrate fertiliser